Readiness on e-Learning application in public higher education institution in Malaysia : a case study on UiTM Shah Alam / Norasyikin Abdul Karim - Abdul Karim, Norasyikin (2005)
This research paper has proposed the discovery of the assessment on readiness towards e-leaming application among degree students in Universiti Teknologi Mara, Shah Alam. E-leaming has been introduced in UiTM since 1999, which known as Flexible Learning Program (FLP) or e-PJJ. This program is mainly handled by InED (Institute of Education Development), which has been set up to manage the centre of educational development. The program that had been offered in FLP is more to the Business and Accounting programs in Diploma and Degree level. To extend more in e-leaming programs in UiTM, it is important to know level of students' readiness towards it. Other than that, it is also important to know the suitable syllabus to make sure the efficiency of e-leaming programs